Implementing the AICCRA Project Across Kitui, Makueni, and Taita Taveta Counties - Association of Women in Agriculture Kenya (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
ICRISAT organized a training for county extension officers and Trainer of Trainers (ToTs) with the primary objective of increasing production and productivity of Drought Tolerant Crops (DTC) in the arid regions of Kenya. This training held from 8th to 30th August 2023, was conducted across Kitui, Makueni and Taita Taveta Counties. The main focus of the training was to enhance participants' understanding of Good Agricultural Practices (GAPs), quality seed production and post-harvest handling of DTCs, while also providing insights into climate information systems. Additionally, the Association of Women in Agriculture (AWAK) delivered a session informing on the gender-specific impacts of climate change on Unpaid Care and Domestic Work (UCDW).